Sex Differences in the Association of Perceived Ambiguity, Cancer Fatalism, and Health-Related Self-Efficacy with Fruit and Vegetable Consumption. Issue 12 (2nd December 2018) - Welch, Jessica D.; Ellis, Erin M.
Abstract : Adequate fruit and vegetable (FV) consumption is promoted as a means of preventing chronic health conditions, such as cardiovascular disease and cancer. This study investigated whether perceived ambiguity about cancer prevention recommendations, fatalistic beliefs about cancer, and health-related self-efficacy were associated with FV consumption and whether sex moderated these associations. Data from the five most recent waves (spanning 2011 to 2017) of the nationally representative Health Information National Trends Survey ( N  = 16, 965) were used. Participants reported levels of perceived ambiguity, cancer fatalism, health-related self-efficacy, and daily FV consumption. Perceived ambiguity and cancer fatalism were negatively associated with FV consumption, ps <.001, whereas health-related self-efficacy was positively associated with FV consumption, b  = 0.34, p  < .001. Sex moderated these associations, ps <.05. Perceived ambiguity and cancer fatalism were more strongly associated with less FV consumption for men, bs < −0.31, ps <.001, than women, bs < −0.14, ps <.01. In contrast, health-related self-efficacy was more strongly associated with more FV consumption for women, b  = 0.43, p  < .001, than men, b  = 0.26, p  < .001. These results suggest that tailoring health messaging to target sex-specific barriers may improve their effectiveness.